Radio-continuum study of the nearby sculptor group galaxies. Part 3: NGC 7793 at λ=12.2, 6 and 3 cm - Galvin, T.; Filipovic, M.; Tothill, N.; Crawford, E.; O Brien, A.; Seymour, Nick; Pannuti, T.; Kosakowski, A.; Sharma, B. (2014)
We re-examine a series of archived centimetre radio-continuum observations (λ=16, 6 and 3 cm) focusing on NGC 7793 using the Australia Telescope Compact Array. These new images are both very sensitive (σ=0.011 mJy/beam) and feature reasonably high angular resolution (down to <3″). Using these images, a total of 76 discrete radio sources are identified, of which 57 have been classified. We also studied the radio component of the micro-quasar NGC7793-S26 which shows two distinct regions of somewhat steep spectral index (α) between −0.3 and −0.7.